2005
DOI: 10.1093/carcin/bgi016
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of human small airway epithelial cells by ectopic expression of telomerase

Abstract: Two immortalized human airway epithelial cell lines were established by the ectopic expression of human telomerase reverse transcriptase (hTERT). These cell lines have been continuously cultured for >200 population doublings (PDs). They are characterized by an overexpression of hTERT mRNA, elongated telomere length and higher telomerase activity. Early passage of these cells (<20 PDs) expressed the p16 protein at a level comparable to their parental cells. In later passages (>150 PDs), p16 protein was decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 35 publications
4
59
1
Order By: Relevance
“…As shown in this study and reported elsewhere [24], urothelial cells, in common with prostate and small airway epithelial cells [29,30], were immortalised by hTERT over-expression alone. Prior to immortalisation, HU-hTERT populations displayed a lag-phase (p11-p13) characterised by reduced growth rates, without senescence or apoptosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in this study and reported elsewhere [24], urothelial cells, in common with prostate and small airway epithelial cells [29,30], were immortalised by hTERT over-expression alone. Prior to immortalisation, HU-hTERT populations displayed a lag-phase (p11-p13) characterised by reduced growth rates, without senescence or apoptosis.…”
Section: Discussionsupporting
confidence: 86%
“…In agreement with this and observations by Chapman et al [24], we saw a dramatic increase in p16 protein associated with the growth lag around the normal senescence point at passage 12 and growth rate recovery was accompanied by a reduction in p16 expression. In the absence of genomic aberration, these observations fit a scenario in which p16 gene expression is silenced epigenetically, as shown for small airway epithelial cells [30].…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that these factors affected the genomic stability and intracellular signaling in the cells, which may facilitate increased transformation. Human telomerase reverse transcriptase (h-TERT)-immortalized human small airway epithelial cells, which were established in our lab, have the characteristics of normal cells (28). In this study, we used this cell line to study the ability of inorganic arsenic to induce transformation in culture as an in vitro model of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have proven that the ectopic expressions of TERT in cells induce the telomerase activity and lengthen telomeres in human (Bodnar et al 1998;Counter et al 1998;Vaziri and Benchimol 1998;Perrem et al 2001), dog (Techangamsuwan et al 2009) and mouse (Armstrong et al, 2000). Meanwhile, immortalization of cells was successfully performed with the ectopic expression of TERT in epithelial cells of human (Morales et al 1999;Piao et al 2005) and goat (He et al 2009). As a corollary, identification of gene encoding TERT in P. monodon (PmTERT) is of great importance as the envisaged immortalization of shrimp cells could be possible with the ectopic expression of PmTERT.…”
Section: Discussionmentioning
confidence: 99%